2005
DOI: 10.1007/s11011-005-4150-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Antioxidant Status, Protein Concentration, Acetylcholinesterase, (Na+,K+)-, and Mg2+-ATPase Activities in the Brain of Hyper- and Hypothyroid Adult Rats

Abstract: It is a common knowledge that metabolic reactions increase in hyperthyroidism and decrease in hypothyroidism. The aim of this work was to investigate how the metabolic reactions could affect the total antioxidant status (TAS), protein concentration (PC) and the activities of acetylcholinesterase (AChE), (Na+,K+)-ATPase and Mg2+ -ATPase in the brain of hyper- and hypothyroid adult male rats. Hyperthyroidism was induced in rats by subcutaneous administration of thyroxine (25 microg/l00 g body weight) once daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 46 publications
5
28
1
2
Order By: Relevance
“…In a previous in vivo study from our group, conducted on rat whole-brain tissues [28], we found a statistically significant reduction of AChE and Na + ,K + -ATPase activities in hyperthyroid rats, whereas hypothyroid rats exhibited a reduction in AChE activity and an increase in Na + ,K + -and Mg 2+ -ATPase activities. Moreover, in a recent in vivo study of ours [29] that was conducted on adult rat cerebellar and hypothalamic tissues, neither hyper-nor hypothyroidism had any effect on the examined hypothalamic enzymes, whereas in the cerebellum, both hyper-and hypothyroidism induced a statistically significant decrease in the activities of both AChE and Na + ,K + -ATPase.…”
Section: Introductionmentioning
confidence: 59%
“…In a previous in vivo study from our group, conducted on rat whole-brain tissues [28], we found a statistically significant reduction of AChE and Na + ,K + -ATPase activities in hyperthyroid rats, whereas hypothyroid rats exhibited a reduction in AChE activity and an increase in Na + ,K + -and Mg 2+ -ATPase activities. Moreover, in a recent in vivo study of ours [29] that was conducted on adult rat cerebellar and hypothalamic tissues, neither hyper-nor hypothyroidism had any effect on the examined hypothalamic enzymes, whereas in the cerebellum, both hyper-and hypothyroidism induced a statistically significant decrease in the activities of both AChE and Na + ,K + -ATPase.…”
Section: Introductionmentioning
confidence: 59%
“…It has been demonstrated that thyroid dysfunction affected synaptic proteins in adult rats [26]. Thyroid hormone deficiency resulted in the down-regulation of syt-1 expression in rat hippocampus [25,27] and cerebellum [28], and the impairment in hippocampal-dependent tasks of learning and memory [29].…”
Section: Animal Model Of Schmentioning
confidence: 99%
“…There are data indicating that excess thyroid hormones act at multiple levels to cause apoptosis, because this higher level enhances the expression of several death receptors and their ligands, such as TNF-, FasL, proNGF, and proBDNF, resulting in activation of apical caspase-8, which is further amplified through the activation of the p75NRT-mediated pathways (Kumar et al, 2007). Hyperthyroid animals appear to have a shorter lifespan and, at an advanced age, have a myelin deficit (Carageorgiou et al, 2005). It is known that hyperthyroidism increases hepatic protein oxidation, as evidenced by a significant 88% increase in the content of protein hydrazone derivatives 3 days after a T 3 treatment.…”
Section: Hyperthyroidism and The Ros-steady Statementioning
confidence: 99%